Perché lo spazio è cosà¬ importante per le regioni? - Sylos Labini, Giovanni (GEOmedia, 2014)
Space activities are very specific in their ability to produce growth and competitiveness and in their continental dimensions are a strategic asset for the competition and defense, aimed at peaceful way, in a troubled era.